2014
DOI: 10.2310/7290.2014.00014
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Mapping of Vascular Inflammation Using the Translocator Protein Tracer 18F-FEDAA1106

Abstract: Noninvasive imaging methods are required to monitor the inflammatory content of atherosclerotic plaques. FEDAA1106 (N-(5-fluoro-2-phenoxyphenyl)-N-(2-(2-fluoroethoxy)-5-methoxybenzyl) acetamide) is a selective ligand for TSPO-18kDa (also known as peripheral benzodiazepine receptor), which is expressed by activated macrophages. We compared 18F-FEDAA1106 and 2-deoxy-2-[18F]fluoro-d-glucose (18F-FDG, a marker of glucose metabolism) for positron emission tomographic (PET) imaging of vascular inflammation. This was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…In stroke patients, TSPO expression and glial activation is increased in the peri-infarct zone for several weeks following insult (154) while bio-imaging has revealed elevated TSPO expression in inflamed atherosclerotic plaques of the vasculature (155,156). …”
Section: Inflammatory Brain Conditionsmentioning
confidence: 99%
“…In stroke patients, TSPO expression and glial activation is increased in the peri-infarct zone for several weeks following insult (154) while bio-imaging has revealed elevated TSPO expression in inflamed atherosclerotic plaques of the vasculature (155,156). …”
Section: Inflammatory Brain Conditionsmentioning
confidence: 99%
“…Novel TSPO-targeting tracers have been studied in preclinical settings to overcome this problem. For example, 18 F-FEDAA1106 has been evaluated in the imaging of the carotid artery cuff model in mice [ 23 ] and 11 C-PBR28 in a rat model of aortic aneurysm [ 24 ]. Both of these studies showed noticeable tracer uptake in lesion areas.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of TSPO is upregulated by exposure to modified LDL in human macrophages [153] and in microglia by lipopolysaccharide (LPS) [154], and TSPO ligands have been used to image macrophage burden and intraplaque inflammation within human and murine atherosclerotic lesions [155][156][157]. Transient overexpression of TSPO in human macrophages enhanced efflux of cholesterol to apoA-I, HDL, and human serum, while knockdown of TSPO achieved the reverse [153].…”
Section: Mitochondrial Cholesterol Trafficking In Macrophagesmentioning
confidence: 99%
“…Signaling via TSPO also reduced the production of reactive oxygen species, cytokines, and chemokines in microglia, and promoted phagocytic activity [158][159][160]; TSPO ligands have also proved useful in reducing inflammation and severity of disease in a murine model of multiple sclerosis [161]. Indeed, TSPO has been proposed as a novel target for Alzheimer's disease and neurologic disorders [162][163][164][165], pain [166], vascular disease [153,[155][156][157], and cancer [167], although it is not clear at present how many of the effects ascribed to TSPO are related to its proposed role in mitochondrial cholesterol trafficking. Further, caution is obviously needed in interpreting the reported effects of TSPO and its ligands, given the lack of phenotype recently reported in healthy TSPO(-/-) mice [111,132,133]: it remains to be seen whether loss of TSPO will contribute to macrophage dysfunction in the context of specific disease pathologies.…”
Section: Mitochondrial Cholesterol Trafficking In Macrophagesmentioning
confidence: 99%